INDUCIBLE NITRIC OXIDE SYNTHASE MODULATES ANGIOGENESIS IN ISCHEMIC HINDLIMB OF RAT - Nematollahi, Sedigheh; Nematbakhsh, Mehdi; Haghjooyjavanmard, Shaghayegh; Khazaei, Majid; Salehi, Mohammad (Biomedical papers, 2009)
Background: Angiogenesis plays an important role in maintaining adequate oxygen delivery, and nitric oxide (NO) is a potential regulator of angiogenesis. NO is synthesized through three isoforms of NO synthase (NOS). It is hypothesized that the NO derived from inducible NOS (iNOS) may promote survival of ischemic tissue through angiogenesis. To test this hypothesis, we investigated the effect of iNOS deficiency (by L-NIL) on angiogenesis in a hindlimb ischemia model.Methods: Thirty-two male wistar rats randomly divided into four groups. In groups 1 & 2, hindlimb ischemia was induced by ligation of femoral artery and they received L-NIL and saline respectively. The animals in groups 3 and 4 also received L-NIL and saline respectively without surgical procedure. After 21 days, the serum concentration of nitrite, capillary density and expression of HIF1α were determined.Results: Serum nitrite levels were significantly lower in L-NIL groups (p<0.05). The capillary density in group 1 (ischemia + L-NIL) was significantly different from group 2 (ischemia + saline); group 1: 360.33 extpm 77.02, group 2: 549 extpm 81.85 /mm2 , p<0.05) .In addition, expression of HIF1α was significantly increased in ischemic groups (p<0.05).Conclusion: Selective inhibition of iNOS by L-NIL inhibits angiogenesis in a hindlimb ischemic rat model. In addition, ischemia induces expression of HIF1α in hypoxic tissue.
Keywords: Keywords: Angiogenesis/ Hind limb ischemia/ Nitric oxide/ Inducible nitric oxide synthase (iNOS)/ L-NIL/ Hypoxic inducible factor 1α (HIF1α)